Skazany na karę pozbawienia wolności – studium prawnokryminologiczne - Paleń - Rogożyńska, Paulina (Kortowski Przegląd Prawniczy, 2021)
The purpose of this article is to present the legal and criminological aspects of a person sentenced to imprisonment, by explaining and defining the concept of “convicted person”, as well as introducing the essence of executing a prison sentence. The article has also raised the issue of classification of prisoners and the issue of the division of prisons on the types and kinds, which is essential for the effective implementation of imprisonment to the convicts. In addition, selected aspects related to the impact of imprisonment in prison on the life of the convict in psychological, socio-criminological terms were also discussed. The discussion of all the threads cited above reflects the main premise of this article.